2022
DOI: 10.1017/s0033291722000630
|View full text |Cite
|
Sign up to set email alerts
|

Measuring discrimination experienced by people with a mental illness: replication of the short-form DISCUS in six world regions

Abstract: Background The Discrimination and Stigma Scale (DISC) is a patient-reported outcome measure which assesses experiences of discrimination among persons with a mental illness globally. Methods This study evaluated whether the psychometric properties of a short-form version, DISC-Ultra Short (DISCUS) (11-item), could be replicated in a sample of people with a wide range of mental disorders from 21 sites in 15 countries/territories, across six global regions. The frequency of experienced dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This finding is consistent with other studies worldwide [ 4 , 48 ]. Brohan et al when used (DISCUS) found that the most common experiences of discrimination were being shunned at work and discrimination in making or keeping friends [ 49 ]. The reasons for this could be that employers tend to deter from hiring and retaining mental health patients because of their cognitive and emotional limitations, which cause reduced productivity and increased costs of disability [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is consistent with other studies worldwide [ 4 , 48 ]. Brohan et al when used (DISCUS) found that the most common experiences of discrimination were being shunned at work and discrimination in making or keeping friends [ 49 ]. The reasons for this could be that employers tend to deter from hiring and retaining mental health patients because of their cognitive and emotional limitations, which cause reduced productivity and increased costs of disability [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2019 ; Brohan et al. , 2022 ), and there are now dedicated instruments to assess anticipated discrimination (Gabbidon et al. , 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2019 ; Brohan et al. , 2022 ), and/or the Questionnaire on Anticipated Discrimination (Gabbidon et al. , 2013 )), would help produce the most relevant and reliable findings.…”
Section: Discussionmentioning
confidence: 99%
“…We adapted the original DISCUS, globally validated for people with mental illness, which collects quantitative information on experience of discrimination across 11 life areas. 16 Those who report discrimination are then asked to provide qualitative examples. As the original measure focused on mental illness, we first reviewed DISCUS items to ensure domains were relevant and sufficient for people living with dementia.…”
Section: Methodsmentioning
confidence: 99%
“…The Discrimination and Stigma Scale Ultra Short (DISCUS) is an existing tool that assesses the scope and context of experienced discrimination among people with mental health conditions, and has previously demonstrated excellent reliability and factor structure in large global samples. 15 , 16 We sought to adapt the DISCUS for people living with dementia, to address the aforementioned research gaps and test its psychometric properties. We refer to the adapted instrument as the Discrimination and Stigma Scale Ultra Short for People Living with Dementia (DISCUS-Dementia).…”
mentioning
confidence: 99%